2018
DOI: 10.1039/c7ta07324k
|View full text |Cite
|
Sign up to set email alerts
|

Copper- and chloride-mediated synthesis and optoelectronic trapping of ultra-high aspect ratio palladium nanowires

Abstract: In hydrothermal synthesis of Pd, Cu(ii) and NaCl enhance yield of 1D nanostructures, which can be optically manipulated in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…65‐6174), respectively . Notably, the interplanar distance of CuO x deposited on PdNWs is slight lower than that of tenorite (copper oxide), revealing its partially oxidized characteristic . Furthermore, the successful coating of CuO x nanocrystals of PdNW@cCuO x was also corroborated by the HAADF‐STEM and corresponding energy dispersive spectrometry (EDS) elemental mappings, as shown in Figure 1f–i, where Cu and O signals are appearing at the external of Pd signal, which consistent well with the line‐scanning results shown in Figure S5 in the Supporting Information.…”
Section: Resultssupporting
confidence: 72%
“…65‐6174), respectively . Notably, the interplanar distance of CuO x deposited on PdNWs is slight lower than that of tenorite (copper oxide), revealing its partially oxidized characteristic . Furthermore, the successful coating of CuO x nanocrystals of PdNW@cCuO x was also corroborated by the HAADF‐STEM and corresponding energy dispersive spectrometry (EDS) elemental mappings, as shown in Figure 1f–i, where Cu and O signals are appearing at the external of Pd signal, which consistent well with the line‐scanning results shown in Figure S5 in the Supporting Information.…”
Section: Resultssupporting
confidence: 72%
“…This approach has advanced rapidly in recent years, and preserves many of the advantages of the conventional methods while being easy‐to‐implement and allowing for cost‐effective operation. Among different optical micromanipulation techniques, optoelectronic tweezers (OET) has proven to be particularly useful for the assembly of large numbers of micro‐ and nano‐objects in parallel, [ 22–31 ] and also for the assembly of micro‐objects with “large” sizes (with at least one dimension greater than 150 µm). [ 32–34 ] However, one limitation for OET assembly (and also for other optical assembly techniques) is that the process must be performed in a fluidic environment, such that the fluid must be removed afterward, often by evaporation, a chaotic process that can destroy the structure that has (up to that point) been carefully assembled.…”
Section: Introductionmentioning
confidence: 99%
“…
These assembly techniques are useful, but they also rely on expensive and specialized positioning tools and well-trained personnel, and can be limited by material properties and throughput.Optical assembly is an alternative strategy to assemble functional structures from micro-and nano-objects as building blocks. [9] Optical assembly relies on optical micromanipulation technologies such as optical tweezers, [9][10][11][12][13] opto-thermophoretic tweezers, [14][15][16] photovoltaic tweezers, [17][18][19][20] and optoelectronic tweezers, [21][22][23][24][25][26][27][28][29][30] in which micro-and nano-objects are optically assembled into a pattern in a fluidic environment and later dried for use in various applications. This approach has advanced rapidly in recent years, and preserves many of the advantages of the conventional methods while being easy-to-implement and allowing for cost-effective operation.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…also has a great impact on the activity of noble-metal nanocrystals. [61][62][63] Nagahiro Hoshi et al 64 studied the effects of different low-index facets of Pd on catalytic activity during the ORR in an acidic medium. The results showed that the ORR activities of different low-index crystal facets follow the order: Pd(111) < Pd(110) < Pd(100), which is completely opposite to the activity order of different low-index crystal facets of Pt.…”
Section: Introductionmentioning
confidence: 99%